1973
DOI: 10.1021/ja00794a042
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-13 nuclear magnetic resonance of 5-substituted uracils

Abstract: 13C chemical shifts and Jc,h coupling constants are reported for 17 5-substituted uracils. Overall, the chemical shifts at C-5 and C-6 of the 5-substituted uracils exhibit no obvious correlation with substituent electronegativity. Instead, when the 5-substituted uracils are considered as trisubstituted ethylenes, the chemical shift data are shown to be rationalized in terms of the ability of the C-5 substituent to behave as a mesomeric acceptor or donor. It is also demonstrated that the correlation of the chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

1976
1976
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 1 publication
2
14
0
Order By: Relevance
“…The N-3, N-5 and N-6 substituted uridines and cytidines included in our present study shown 6(H-6) and 6(H-5) variations which closely parallel the substituent effects observed in the bases. The following upfield and downfield shifts of 6(H-6), relative to the unsubstituted nucleosides, are observed upon C-5 substitution : produced by base substitution reflect electron density changes originating in the C(5) = C(6) half of the pyrimidine itself, in accord with theoretical considerations, I3C nuclear magnetic resonance [34] and photoelectron spectroscopic measurements [35], which agree that uracil is not an aromatic system but that C(5)=C(6) must be regarded as a substituted ethylene or enamine unit. The nucleosides derived from methylated or halogenated uracil and cytosine may then be treated together with unsubstituted uridines and cytidines in the following discussion.…”
Section: Pyrimidine Structuresupporting
confidence: 64%
“…The N-3, N-5 and N-6 substituted uridines and cytidines included in our present study shown 6(H-6) and 6(H-5) variations which closely parallel the substituent effects observed in the bases. The following upfield and downfield shifts of 6(H-6), relative to the unsubstituted nucleosides, are observed upon C-5 substitution : produced by base substitution reflect electron density changes originating in the C(5) = C(6) half of the pyrimidine itself, in accord with theoretical considerations, I3C nuclear magnetic resonance [34] and photoelectron spectroscopic measurements [35], which agree that uracil is not an aromatic system but that C(5)=C(6) must be regarded as a substituted ethylene or enamine unit. The nucleosides derived from methylated or halogenated uracil and cytosine may then be treated together with unsubstituted uridines and cytidines in the following discussion.…”
Section: Pyrimidine Structuresupporting
confidence: 64%
“…Compounds 2-16 were identified as lumichrome (2), 5) chrysoeriol (3), 6) genistein (4), 7) adenosine (5), 8) guanosine (6), 9) uracil (7), 10) acetovanillone (8), 11) vanillin (9), 11) vanillic acid (10), 12) 6-methoxy-benzoxazolinone (11), 13) stigmast-4-en-3-one (12), 14) b-sitosterol (13), 15) stigmasterol (14), 16) stigmastanone (15), 17) and 7a-hydroxysitosterol (16) 18) based on comparison of their NMR spectral data with published spectral data.…”
mentioning
confidence: 99%
“…The calculations predict that almost 90% of the difference in the u + H electron density at the 6 position that occurs between uracil and 5-fluorouracil arises from the difference in electron density of the orbital. Table I also contains chemical shift data from CI3 N M R studies of the C(6) atom in uracil, thymine, 5-fluorouracil, and CF3U [43]. As the magnitude of the chemical shift decreases, the electron shielding at the C(6) atom is expected to decrease.…”
Section: Resultsmentioning
confidence: 99%
“…In a preliminary attempt to predict the relative susceptibility of uracil and substituted uracils to nucleophilic attack the magnitude of the total electron density at the 6 position has been considered [43]. From this point of view the INDO calculations and the N M R results predict that the susceptibility to nucleophilic attack of the C(6) atom in the molecules studied increases in the order 5-fluorouracil < thymine < uracil < CF,U.…”
Section: Resultsmentioning
confidence: 99%